Development of patient-specific iPSC-based epilepsy models and identification of differentially expressed genes for disease mechanisms - Wu, Jianfeng; Huang, Siqi; Chen, Lihao; Yang, Yinghong; Zhang, Shunhan; Xian, Jiajia; Ma, Xiaoyan; Ma, Furong; Li, Shaoying; Yang, Yi; Xie, Yingjun; Sun, Xiaofang (Frontiers in Neuroscience, 2025)
IntroductionEpilepsy is a complex neurodegenerative disorder characterized by recurrent seizures, which poses significant challenges for clinical management and therapeutic development. Recent advances in stem cell biology have enabled the use of patient-specific induced pluripotent stem cells (iPSCs) as a novel in vitro model for studying human diseases, including neurological disorders. In particular, iPSCs offer a promising platform for investigating the molecular mechanisms of epilepsy and facilitating personalized medicine.MethodsIn this study, we generated iPSC lines from individuals diagnosed with epilepsy who carry a novel mutation in the CLCNKB gene. These patient-derived iPSCs were reprogrammed from somatic cells and subsequently characterized. To explore the molecular alterations associated with epilepsy, we performed transcriptomic profiling using RNA sequencing (RNA-seq). Differential gene expression analysis was conducted to compare the patient-derived iPSCs with control iPSC lines.ResultsThe RNA-seq analysis revealed a set of differentially expressed genes in epilepsy-derived iPSCs, with both upregulated and downregulated genes identified relative to controls. Several of these genes have previously been implicated in epilepsy-related phenotypes, as supported by published literature. This suggests a potential role for these genes in the pathophysiology of epilepsy linked to CLCNKB mutations.DiscussionThe successful establishment of CLCNKB-mutant patient-specific iPSC lines and their transcriptomic characterization provide a valuable tool for studying the molecular basis of epilepsy. These findings underscore the potential of iPSC-based models to advance our understanding of disease mechanisms and support the development of novel diagnostic and therapeutic strategies. Moreover, this study demonstrates the applicability of iPSCs for epilepsy research and their promise in the field of personalized medicine.